INVESTIGATING STUDENTS’ ENTHUSIAST ON THE USE OF GOOGLE CLASSROOM BY EIGHT SEMESTER OF UNISMA - Nurlatifah Islami (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
Google Classroom is one of an appropriate learning management system made by Google Company to facilitate teaching and learning process especially for the current situation. One of the most characteristics that learners must have even in this era is enthusiasm. This study was attempted to prove whether virtual learning toward Google Classroom can increase students’ level of enthusiasm or not. This research was conducted in University of Islam Malang with 34 respondents in the 8th semester who had experienced in learning activity by using Google Classroom. The design of this study was descriptive qualitative design. The data were obtained through questionnaire and interview. To analyze the data questionnaire, Google Form was used. According from the first finding, it was proven that Google Classroom is one of an effective platform made as a substitute for offline learning. On the contrary, to prove that Google Classroom can increase students’ enthusiast, the researcher cannot prove it. Then for the second finding, there are several factors that can influence student level of enthusiasm such as interesting features, passion, environment support, and develop knowledge. The last finding which was the researcher found that problem faced in using this platform such as less interactive, signal, internal problems and external problem.            Based on the data result, it is known that enthusiasm is the most specific aspect must have for both of the students and lecturer. To make the students felt enthusiast in virtual learning should be start from the lecturer first. If the lecturers are enthusiast, the students will be enthusiast. And the suggestion for the next researchers, the researcher hope they can find the strategies to enhance students’ enthusiast in learning process on the use of Google Classroom.Keywords: Online Learning, Google Classroom, Enthusiasm